Pengaruh Integritas dan Profesionalisme Kerja terhadap Kualitas Pelayanan Publik - Pratamireza Putri Lase (Journal of Education on Social Science (JESS), 2021)
Integrity and professionalism of an employee was one of indicators to improve the quality of public services. The existence of problems with the quality of public services at the Pariaman City District Court Office which was still low indicated the integrity and professionalism of employees was needed to improve the quality of public services in the agency of Pariaman City District Court. This research was conducted in order to improve the trust and legitimacy of the government and its bureaucracy in the eyes of the public. To achieve this goal, the researchers used data collection techniques through the distribution of questionnaires with a population of 39 people. The data was processed using quantitative analysis to determine the effect of employee integrity and professionalism on the quality of public services. From the results of this study, it could be seen that there was a positive influence on the integrity and professionalism of employees' work on the quality of public services which has been tested by the T test, the X1 variable against Y has a significance value of 0.017 <0.05. and the T-test of the X2 variable against Y had a significance value of 0.000 <0.05. And the percentage contribution of the variable X to Y is 49.4%. The value listed in this study was the higher the integrity and professionalism of the employee's work, the higher the quality of public services provided